A Case Report of Kartagener Syndrome - Mahnaz Moradi (The Journal of Qazvin University of Medical Sciences, 2020)
Primary Ciliary Dyskinesia (PCD) and Kartagener Syndrome (KS) are rare genetic disorders. PCD occurs in patients with recurrent sino-pulmonary infection, dextrocardia, chronic vasomotor rhinitis, and bronchiectasis. This study reports a rare case of KS for having further awareness of this disease. According to this study, this disease should be considered in patients with recurrent respiratory infections, because early diagnosis and timely treatment of these patients can lead to reduced irreversible complications and increased life expectancy.